Julia Lesage: “I was never anything less than the person I am.” An Interview with the Author, Editor, and Filmmaker Julia Lesage (Konturen, 2022)
An interview with Julia Lesage, pioneering experimental filmmaker and scholar of feminist documentary theory, conducted by Sonja Boos on 16 January, 2020.